พฤติกรรมการปฏิบัติงานของบุคลากร การไฟฟ้าส่วนภูมิภาคประตูน้ำพระอินทร์ อำเภอบางปะอิน จังหวัดพระนครศรีอยุธยา - เสือป่า, สุนิสา; แสนภูมี, สมชัย (วารสาร มมร ยศสุนทรปริทรรศน์, 2025)
This study aimed to: 1) To study the work behavior of the personnel of the Provincial Electricity Authority, Pratunam Phra In. 2) To compare personal factors and work behavior of the personnel of the Provincial Electricity Authority, Pratunam Phra In. The population and sample used in the research are the personnel of the Provincial Electricity Authority, Pratunam Phra In, totaling 70 people. The sample size is 59 people using the ready-made sample size table of Krejcie and Morgan (1970). The research instrument is a questionnaire. The statistics used for data analysis are percentage, mean, standard deviation, and inferential statistics. The results of the research found that 1) The work behavior of the personnel of the Provincial Electricity Authority, Pratunam Phra In, Bang Pa-in District, Phra Nakhon Si Ayutthaya Province, overall is at the highest level with an average value of X ̅ = 4.55, S.D. = 0.54, which is at the highest level. When classified into the highest aspect, honesty has an average value of X ̅ = 4.88, S.D. = 0.26, which is at the highest level. Next is prudence, with an average of X ̅ = 4.76, S.D. = 0.45, at the highest level. Next is discipline, X ̅ = 4.44, S.D. = 0.68, at a high level. Next is responsibility, X ̅ = 4.36, S.D. = 0.70, at a high level. And the least is good attitude, with an average of X ̅ = 4.33, S.D. = 0.61, at a high level. 2) The difference in factors of work behavior of the personnel of the Provincial Electricity Authority, Pratunam Phra In, Bang Pa-in District, Phra Nakhon Si Ayutthaya Province, found that personal factors affecting the work behavior of the personnel of the Provincial Electricity Authority, Pratunam Phra In, Bang Pa-in District, Phra Nakhon Si Ayutthaya Province were not different.